Sustainable Design Practice of University Library Building: Take the Guangdong University of Finance & Economics Library as an example - Liu, Qionglin; Chen, Jun; Wu, Kairui; Du, Shuwei (IOP conference series. Earth and environmental science, 2019)
Designing and building sustainable buildings is a trend in the current building industry. Utilizing intensive land resources, three-dimensional greening, integration of architectural design, water resources utilization, optimization of indoor acoustic environment and comfort, education promotion and other sustainable development technical measures, the green building design practice of Guangdong University of Finance & Economics Guangzhou Campus combines the local climate characteristics and organically combines green building design practice with cultural education building, which can provide theoretical and practical references for the design practice of green culture education buildings in China.